2021
DOI: 10.1002/htj.22388
|View full text |Cite
|
Sign up to set email alerts
|

Generalized differential quadrature analysis of electro‐magneto‐hydrodynamic dissipative flows over a heated Riga plate in the presence of a space‐dependent heat source: The case for strong suction effect

Abstract: The importance of including an electromagnetic actuator as a moving boundary on the dissipative flows of weakly conducting fluids had led to many published facts. But, nothing is known on the generalized differential quadrature analysis of magnetohydrodynamics over a Riga plate with emphasis on the case of viscous dissipation and space-dependent heat source.After deriving the simplified boundary layer equation that models the transport phenomenon, appropriate variables were used to non-dimensionalize and param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It has been determined that the wall suction impact increases the heat exchange efficiency and thermodynamic irreversibility toward the Riga plate, whereas the increasing intensities of the magnetic field have the opposite feature. [37][38][39] Generally, for heat transfer by natural or forced convection process, water, ethylene glycol, and mineral oils were used as a convective medium. But these types of fluids show low thermal conductivity, which does not satisfy the satisfactory demand level to be an effective heat transfer medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that the wall suction impact increases the heat exchange efficiency and thermodynamic irreversibility toward the Riga plate, whereas the increasing intensities of the magnetic field have the opposite feature. [37][38][39] Generally, for heat transfer by natural or forced convection process, water, ethylene glycol, and mineral oils were used as a convective medium. But these types of fluids show low thermal conductivity, which does not satisfy the satisfactory demand level to be an effective heat transfer medium.…”
Section: Introductionmentioning
confidence: 99%
“…Different academics have lately investigated the EMHD boundary layer occurrence on non‐Newtonian fluid under the action of numerous physical phenomena. It has been determined that the wall suction impact increases the heat exchange efficiency and thermodynamic irreversibility toward the Riga plate, whereas the increasing intensities of the magnetic field have the opposite feature 37–39 …”
Section: Introductionmentioning
confidence: 99%
“…To control the heat transmission rate for fluid flow past a stretched sheet, Bataller 33 used a variable heat source with viscous dissipation and observed that thermal profiles were supported by Eckert number, radiation, and dissipation parameters. Zaydan et al 34 inspected EMHD dissipative fluid flow past a heated Riga plate using a heat source. Khan et al 35 analyzed nanofluid flow over a spinning needle employing viscous dissipation and magnetic effects to the flow system.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other studies of heat transfer are presented in Refs. [39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%